Sonaf and the Uab Meto Belief: Social Space and Local Wisdom in Maintaining Interfaith Harmony on Timor Island East Nusa Tenggara - Bagus Muhammad Ilham; Nur Nafisa Salsabila (Journal of Science and Research, 2026)
Religion and belief are two inseparable elements, particularly in the context of the Indonesian archipelago. Long before the widespread dissemination of conventional religions, shaped by factors such as history, culture, politics, and other influences, these indigenous beliefs were prevalent and are often referred to as Prehistoric Religion. The communities of East Nusa Tenggara (NTT), especially on Timor Island, uphold a belief in a supreme power and supernatural elements, such as the Sky God (Uis Neno) and Earth God (Uis Afu). Archaeological remnants of prehistoric artifacts on Timor Island indicate that the local belief system is characterized by dynamism and animism, as practiced by the Atoni Meto, Dawan, and Helong ethnic groups inhabiting the Timor plains. The research question addressed in this study is how the concepts of Sonaf and Uab Meto are understood and interpreted within historical and cultural contexts. Using a cultural-historical approach and historical methods including heuristics, verification, interpretation, and historiography, this study investigates the phenomenon of syncretism, whereby conventional religions gradually entered and blended with prehistoric belief systems. The findings reveal that communities in the interior were influenced by other groups through cultural diffusion or assimilation, resulting in the emergence of new beliefs or streams derived from multiple religious traditions. Religious inculturation, as a process of integrating religious values and practices with local wisdom, allows religion to become relevant and comprehensible to local communities. This study contributes to the field of cultural history, particularly in understanding the dynamics of social structure, political organization, and spirituality in Timorese society, while also expanding knowledge of the rich cultural diversity present in Indonesia.